Development of information technology for heat losses management of construction structures - Yerokhin, Andriy; Zatserklyanyi, Heorgiy (Technology audit and production reserves, 2019)
The object of research in this work is unproductive heat loss in buildings and construction structures; due to the nature of the heat and mass transfer process; which operates in a complex architectural and structural scheme. One of the ways to reduce unproductive heat losses in buildings and construction is the use of information and control technologies and systems for managing such objects. These technologies and systems based on information processing on the state of buildings and construction facilities should ensure the formation of effective managerial decisions aimed at reducing unproductive heat losses and optimizing the structure of consumption of fuel and energy resources in the housing and communal sector. Today; both in the energy efficiency control systems of buildings and outside of their heat and mass transfer processes; they are analyzed either in a simple statement or in separate elements of the architectural design of a building structure. Such an approach to modeling the heat and mass transfer process does not provide a sufficiently complete assessment of unproductive heat loss. This is due to the fact that the process of heat and mass transfer is a complex interconnected and interdependent system and operates in a complex architectural and structural system of a building structure. In this paper; a component-oriented information technology is proposed that relies on a mathematical model of an interconnected and interdependent heat and mass transfer process that operates in any complex architectural and structural scheme of a house or building structure. This model; in comparison with other models used; covers all the basic properties of heat and mass transfer both in building envelopes and in vapor-air spaces. It takes into account the heat input to the house from heating and lighting systems; solar radiation and people in the building. So; it allows to more fully evaluate the heat loss in a house or building.